ChemInform Abstract: "On Water" Synthesis of Highly Functionalized 4H‐Chromenes via Carbon—Carbon Bond Formation under Microwave Irradiation and Their Antibacterial Properties. Issue 34 (August 2015) - Rao, L. Chandrasekhara; Kumar, N. Satish; Dileepkumar, V.; Murthy, U. S. N.; Meshram, H. M.
Abstract The antibacterial activity of the products is evaluated.